PROBLEM SOLVING TECHNIQUES AS AN ATTEMPT TO IMPROVE THE ADAPTABILITY ABILITIES OF GRADE 7 STUDENTS - Ramadhan, Manhaereiza Putri Lyanta; Sari, Eva Kartika Wulan; Ariffudin, Imam (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
Lack of adaptation is a common problem experienced by students, especially when they enter a new school environment. Students may face various challenges during this adjustment period, making it important for schools to provide professional services that help enhance students’ adaptability skills in their new surroundings. The aim of this study was to examine whether group guidance with the problem-solving technique could enhance students’ adaptability skills.This research employed a quantitative approach with an experimental method using a one-group pre-test and post-test design. The research subjects consisted of 10 students selected through a stratified random sampling technique. The instrument used was an adopted adaptability skill scale. Based on the analysis results, it can be concluded that there was an improvement in students’ adaptability skills, with an average score increase of 8.2 points. The findings indicate that group guidance with the problem-solving technique effectively enhances students’ adaptability skills